2021
DOI: 10.7150/jca.57831
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Significance of BTN3A Proteins in Tumors

Abstract: The Butyrophilin 3A (BTN3A) family is a type I transmembrane protein belonging to the immunoglobulin (Ig) superfamily. The family contains three members: BTN3A1, BTN3A2 and BTN3A3, which share 95% homology in the extracellular domain. The expression of BTN3A family members is different in different types of tumors, which plays an important role in tumor prognosis. Among them, there are many studies on tumor immunity of BTN3A1, which shows that it is essential for the activation of Vγ9Vδ2 T cells, while BTN3A3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Therefore, it is reasonable to hypothesize that a high expression of IFIT2 plays a role in the anti-ESCC process. The role of BTN3A3 is expected to become a potential therapeutic target for breast cancer (30), and the upregulation of BTN3A3 has been significantly correlated with better overall and relapse-free survival (31). Moreover, it has been noted to be a novel prognostic factor for hepatocellular carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to hypothesize that a high expression of IFIT2 plays a role in the anti-ESCC process. The role of BTN3A3 is expected to become a potential therapeutic target for breast cancer (30), and the upregulation of BTN3A3 has been significantly correlated with better overall and relapse-free survival (31). Moreover, it has been noted to be a novel prognostic factor for hepatocellular carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…BTN3A1 belongs to the BTN3A family, which is part of a type I transmembrane protein of the immunoglobulin (Ig) superfamily. The expression levels of BTN3A family members are different among various tumours, which has a crucial impact on tumour prognosis 23 . In patients with melanoma, the expression of BTN3A is increased in pDC cells and γδ T cells; dysfunctional BTN3A leads to defective interaction between pDC and γδ T cells, affecting clinical results 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Yamashiro et al found that the expression level of BTN3 was inversely correlated to the activity of lymphocytes, and administration of the mAb 232-5 lead to phosphorylation of the BTN3A3 molecule and transduction of negative signals; these effects caused CD4+ and CD8+ T cells to act like CD4 + CD25+ Tregs, accompanied by a decrease in cell proliferation and cytokine secretion [ 157 ]. However, the mAb 20.1 has no significant stimulatory or costimulatory effect on αβT cells [ 154 ], suggesting that BTN proteins may jointly inhibit effector T cells through negative signal transmission and that BTN3A3 may be a novel target [ 158 ]. In addition, although the mAb 103.2 does not affect the proliferation and activation of CD8+ T cells, it can inhibit the response of γδT cells induced by PAgs and even inhibit the degranulation and cytokine secretion of Vγ9Vδ2T cells, decreasing their antitumor effects.…”
Section: Targeting Ics Can Regulate the Immune Function Of γδT Cellsmentioning
confidence: 99%